Sensitivity Calculation of Different Parameters for Power Plant Collaboration - Yang, Ziqi (My University, 2014)
This paper introduces a dynamic simulation method to simulate a WECC 4 bus power plant model and discusses various optimization approaches to better simulate the model by varying some parameter values.
Keywords: Block Diagram Conversion; Control Modeling; Dynamic Simulation; Perturbation Analysis; Power System Modeling; Sensitivity Analysis